Role of angiogenesis in the pathogenesis of arthritis: Potential therapeutic applications - Kiriakidis, S; Paleolog, E (Springer Netherlands, 2011)
Rheumatoid arthritis (RA) is a chronic systemic inflammatory disease, associated with inflammation of the synovial lining of tendons and joints. Despite major advances in the treatment of RA, using biological therapies, particularly treatments targeted at cytokines such as tumour necrosis factor α (TNFα), there is still a significant unmet need in RA, due to non-responders and increased infections following TNFα blockade. Dysregulated angiogenesis contributes to diseases associated with excessive vascularisation, such as cancer and certain forms of ocular disease, and has recently been linked to RA. A number of pro- and anti-angiogenic factors are expressed in RA synovium, including vascular endothelial cell growth factor (VEGF). As is the case in cancer, hypoxia is a feature of RA, and the hypoxia/Hypoxia inhibitors factor (HIF) pathway and HIF target genes, particularly VEGF, contribute to RA severity. Therefore, angiogenesis and HIF inhibitors that are already in use against cancer could also be potential candidates for the treatment of RA. In RA, therapies aimed at inhibiting angiogenesis, such as inhibitors of VEGF, have shown efficacy in animal models of arthritis. It is therefore possible that in the future, treatments such as bevacizumab may prove to be beneficial in RA in combination with existing modalities such as TNFα inhibition. © 2011 Springer Science+Business Media B.V.